Plasticity of morphological paradigms - Rodrigues, Alexandra Soares (2020)
The aim of this work is to explain, in a paradigmatic framework, the occurrence of event nouns with the suffix - ação having an intensive/iterative meaning in Brazilian Portuguese, which does not occur in European Portuguese (e.g., viajação ‘intensive and iterated travel’, passeação ‘intensive and iterated walk’). The paradigmatic approach to word formation has been recently reinforced against rule conceptions. Studies such as Štekauer 2014; Antoniová and Štekauer 2015; Blevins et al. 2019; Blevins 2016; Booij 2007; Baeskow 2015; Ortner and Ortner 2015; Spencer 2013; Fradin 2018 have emphasised the domain of word formation as a mental network of paradigms, against the vision that only inflection operates paradigmatically. The aim of this study is to bring experimental and empirical evidence to the plasticity of word-formation paradigms. Paradigms are conceived of as dynamic patterns mentally organised in networks. The relationships between items that build a paradigm may be of different types, as highlighted by Pounder (2000), Štekauer (2014) or Van Marle (1985). Following Rodrigues and Rodrigues (2018), we call the axis of the paradigm the feature that is responsible for the cohesion of the paradigm, i.e., for the relationship between the items belonging to the paradigm. We will focus on paradigms organised around different axes. The axis of one of the paradigms is the relationship between the syntactic and the semantic categories (which Bonami & Strnadová 2019 call content) of the involved members of the pairs of the paradigm, specifically event/result/state noun1 verbs (Table 1). We call this kind of paradigm a categorial macro-paradigm (built upon a macro-pattern). Micro-paradigms result from specialisations (Lindsay & Aronoff 2013, Aronoff & Lindsay 2014, 2015, Aronoff 2016, Rodrigues in press) and selectional restrictions inside the categorial macro-paradigm.